An ad hoc distributed systems approach for industrial wireless sensor network management - Gholami, M.; Taboun, M.S.; Brennan, R.W. (Journal of industrial information integration, 2019)
This paper reports on an ad hoc wireless sensor network architecture for industrial sensing and control applications. This approach is tested using a large-scale (400–676 node) agent-based simulation of a factory environment that is subject to noise and blockage. The basic problem tackled by the distributed system is mobile node tracking. To support this work, we introduce two classes of metrics: (1) a set of tracking performance metrics, and (2) a set of network architecture efficiency metrics. The results of our experiments show that the proposed distributed system adapts readily to changes in the sensing environment, but this higher level of adaptability is at the cost of overall efficiency.